First Results of the LUX Dark Matter Experiment - LUX collaboration (86 authors) (2016)
LUX (Large Underground Xenon) is a dark matter direct detection experiment deployed at the 4850' level of the Sanford Underground Research Facility (SURF) in Lead, SD, operating a 370 kg dual-phase xenon TPC. Results of the first WIMP search run were presented in late 2013, for the analysis of 85.3 live-days with a fiducial volume of 118 kg, taken during the period of April to August 2013. The experiment exhibited a sensitivity to spin-independent WIMP-nucleon elastic scattering with a minimum upper limit on the cross section of 7.6×10−46cm2 at a WIMP mass of 33 GeV/c 2 , becoming the world's leading WIMP search result, in conflict with several previous claimed hints of discovery.